Giant pleomorphic adenoma of the parotid gland: a case report - Ernesto Carmona Fernàndez (South Sudan Medical Journal, 2021)
Pleomorphic adenomas account for the majority of parotid masses, typically arising in the tail of the gland and enlarging slowly. Most are 2 to 6 cm in size when resected. We report the resection of a benign mixed tumour of the left parotid gland with a history of bleeding. The resected tumour measured 21 cm in diameter, weighed 1.81 kg, and on pathologic examination was a benign mixed tumour without malignant degeneration. The implications of this unusual case for the management of mixed tumours are discussed with a review of the literature